Self-defensive gun use by crime victims: a conjunctive analysis of its situational contexts - Hart, Timothy C. (Journal of contemporary criminal justice, 2009)
As a means for analyzing categorical data, conjunctive analysis is an emerging analytic approach used in both exploratory and confirmatory research. This technique is applied in the current study to examine two important issues related to the use of firearms as a means of self-defense by crime victims. Using data from the National Crime Victimization Survey, the current study uses conjunctive analysis (a) to examine the contextual factors associated with the use of a firearm by crime victims as a means of self-defense and (b) to identify the situational factors most closely associated with instances where the self-defensive use of a firearm is most and least effective. Results are discussed in terms of their implications for future research.